Can a two-hour lecture by a pharmacist improve the quality of prescriptions in a pediatric hospital? A retrospective cohort study - Carceller-Blanchard, Ana; Vairy, Stéphanie; Corny, Jennifer; Jamoulle, Olivier; Levy, Arielle; Lebel, Denis (Canadian Medical Education Journal, 2017)
Background: A high rate of prescription errors exists in pediatric teaching hospitals, especially during initial training. Objectives: To determine the effectiveness of a two-hour lecture by a pharmacist on rates of prescription errors and quality of prescriptions. Methods: A two-hour lecture led by a pharmacist was provided to 11 junior pediatric residents (PGY-1) as part of a one-month immersion program. A control group included 15 residents without the intervention. We reviewed charts to analyze the first 50 prescriptions of each resident. Results: Data were collected from 1300 prescriptions involving 451 patients, 550 in the intervention group and 750 in the control group. The rate of prescription errors in the intervention group was 9.6% compared to 11.3% in the control group (p=0.32), affecting 106 patients. Statistically significant differences between both groups were prescriptions with unwritten doses (p=0.01) and errors involving overdosing (p=0.04). We identified many errors as well as issues surrounding quality of prescriptions. Conclusion: We found a 10.6% prescription error rate. This two-hour lecture seems insufficient to reduce prescription errors among junior pediatric residents. This study highlights the most frequent types of errors and prescription quality issues that should be targeted by future educational interventions.